1994
DOI: 10.1046/j.1365-2648.1994.20050950.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected predictors of registered nurses' intent to stay

Abstract: This paper reports initial findings from a longitudinal study of autonomy, willingness to risk, exit/voice (E/V) and managerial environment (ME) as predictors of registered nurses' intent to stay (ITS) that is being conducted at eight Midwestern hospitals in the USA. In this two-stage study, initial findings are based on responses from 524 staff nurses. Due to the nature of the ITS variable, two logistic regression analyses were computed to test the predictive relationships of the independent variables. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 19 publications
2
40
2
Order By: Relevance
“…This finding is contrary to those of Friss (1982), Schaefer, (1989, Diaz (1989) Fisher, Hinson, & Deets (1994, and Shay & Stallings (1993) who all noted a correlation between turnover and education levels. This does not negate the importance of continuing education but it may indicate that nurses want continu ing education to keep their skills sharp and to learn new techniques; the acquisition of a degree beyond the diploma level may not matter to them provided they have educa tional opportunities given to them.…”
Section: Education Levelcontrasting
confidence: 69%
See 3 more Smart Citations
“…This finding is contrary to those of Friss (1982), Schaefer, (1989, Diaz (1989) Fisher, Hinson, & Deets (1994, and Shay & Stallings (1993) who all noted a correlation between turnover and education levels. This does not negate the importance of continuing education but it may indicate that nurses want continu ing education to keep their skills sharp and to learn new techniques; the acquisition of a degree beyond the diploma level may not matter to them provided they have educa tional opportunities given to them.…”
Section: Education Levelcontrasting
confidence: 69%
“…Friss (1982), While & Blackman (1998) and Leveck & Jones (1996) state that age and experience are fac tors in retention; the older a nurse is and the longer she has been at an institution, the less likely she is to leave. Shay & Stallings (1993), Fisher, Hinson & Deets (1994, Diaz (1989), Schaefer (1989), andFriss (1982) also note that there is a correlation between turnover and level of skill, education opportunities and type of occupation.…”
Section: Factors Related To Retention Of Nurses In Hospitalmentioning
confidence: 99%
See 2 more Smart Citations
“…T h e se studies exam ined the effect that leadership styles had on job satisfaction (M cNeese-Smith, 1997; Morrison, Jo n es, & Fuller, 1997) and the effect of leadership styles on the n u rse s' intent to stay (Fisher, Hinson, & D eets, 1994). All three identified that participatory and considerate supervision en h an ced job satisfaction.…”
mentioning
confidence: 99%